2018
DOI: 10.3389/fendo.2018.00537
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Human Peripheral Mononuclear Cells Phenotype Markers in Type 2 Diabetic Patients and Type 2 Diabetic Patients on Metformin

Abstract: Background: Although peripheral blood mononuclear cells (PBMC) have been demonstrated to be in a pro-inflammatory state in obesity and type 2 Diabetes Mellitus (T2DM), characterization of circulating PBMC phenotypes in the obese and T2DM and the effect of Metformin on these phenotypes in humans is still ill-defined and remains to be determined.Methods: Thirty normal healthy adult volunteers of normal weight, 30 obese subjects, 20 obese newly diagnosed diabetics and 30 obese diabetics on Metformin were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…18 However, the ability of NAMPT to trigger IL-6/STAT3 cell survival pathway did not depend on the presence of nicotinamide and was not blocked by the NAMPT enzyme inhibitor FK866. 18 Thus, inhibition of NAMPT expression in PBMC and the higher expression levels of IL-6 previously reported 19 in our study support the notion that these pathways are regulated independently. Endothelial dysfunction is a characteristic of agingrelated vascular disease and is worsened during diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…18 However, the ability of NAMPT to trigger IL-6/STAT3 cell survival pathway did not depend on the presence of nicotinamide and was not blocked by the NAMPT enzyme inhibitor FK866. 18 Thus, inhibition of NAMPT expression in PBMC and the higher expression levels of IL-6 previously reported 19 in our study support the notion that these pathways are regulated independently. Endothelial dysfunction is a characteristic of agingrelated vascular disease and is worsened during diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, an accumulation of the nonclassical monocytes, in conjunction with higher levels of plasma TNFα and interleukin-8 (IL-8), has been observed in the elderly. 32 Our previous study has shown that PBMC from T2DM subjects have increased expression of IL-6, inducible nitric oxide synthase (iNOS), TNFα, CD36, and CD206 and reduced expression of CD11b, CD11c, CD169, and CD163 (19). Other studies have demonstrated an increased inflammatory state in obesity and T2DM.…”
Section: Discussionmentioning
confidence: 97%
“…The phagocytic activity of MOs is the subject of several studies under normal and pathological conditions including breast cancer (53). In our study, we observed that pretreatment with MET downregulated the phagocytic capacity of MOs, which is of interest, knowing that high phagocytic capacity is associated with MOs that promote survival and extravasation of cancer cells, and characterizes the so-called 'classical MOs' in humans (54,55).…”
Section: Discussionmentioning
confidence: 64%
“…The phagocytic activity of MOs is the subject of several studies under normal and pathological conditions, including breast cancer [ 51 ]. In our study, we observed that pretreatment with MET downregulated the phagocytic capacity of MOs, which is of interest, knowing that high phagocytic capacity is associated with MOs that promote survival and extravasation of cancer cells, and characterizes the so-called ’classical MOs’ in humans [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%